UNITED NATION CHILDREN’S FUND (UNICEF) DALAM INTERVENSI KEMANUSIAN PADA KONFLIK SURIAH TAHUN 2011-2015 - Indah Fitria; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explaining about humanitarian intervention of United Nation Children’s Fund (UNICEF) in Syria Arab Republic conflict that began in 2011. Syria president, Bashar al-Assad protested by Syrian in March of 2011. Assad government used arm forced to handle the protester which led conflict started to blow up. Since the conflict began Syrian children faced situations that risk their right. Children were killed shot by gun, explosive shelling, detention and executions, deprivated by medical serviced and others. Conflict itself affect children mental health and in need of phycosocial service. Syrian children have limited acces for their basic need.This research use Pluralism perspective of International Relations. Pluralism believe state is not the only actor in international world. This research is also guide by international organization theory and role concept. Fact, data, arguments, and theorical framework of this research formulate by using qualitative description.UNICEF has keep it focus on violation of Syirian children’s right during the conflict and the effect of the humanitarian crisis to the children. UNICEF operate programes such children protection, work with other humanitarian actors for Syrian Humanitarian Respon Plan, suggest No lost Generation inititative in education sector and complete by humanitarian action in Health, WASH and Non Food Item sectors. UNICEF work in Syria increased children rights perfomance during conflict and ensure humanitarian action implementations.Keywords : UNICEF, Children Protection, Humanitarian Respon Plan